Time History of a Human Kidney Stone Determined by Bomb-Pulse Dating. Issue 2 (6th January 2016) - Levchenko, Vladimir A; Williams, A Alan
Abstract: An in vivo grown human kidney stone was dated using the atmospheric bomb pulse. The growth period was found to be 17.6 yr for a sample size of 6 mm across. The step dissolution method was used, as one of several possibilities, to produce depositional subsamples. A noticeable dead carbon presence is detected in the modern industrialized diet, and as a consequence in human metabolites. The importance for correction when applying bomb-pulse dating is noted.